Acid Red 88 biodegradation by Cu nanoparticles stabilized on Marinospirillum alkaliphilum strain N - Samira Eshghi; Fereshteh Jookar Kashi (Scientific Reports)
Abstract In recent years, Cu nanoparticles (CuNPs) have emerged as a widely used and cost-effective tool, especially in analytical fields. This study investigates the biological properties of CuNPs synthesized by strain Cu1 and their efficiency in degrading Acid Red 88 dye. Additionally, it evaluates the potential of a novel combination of Marinospirillum alkaliphilum strain N and CuNPs for AR88 biodegradation. Strain Cu1, a copper-resistant strain from the Sungun copper mine, was used for biosynthesizing CuNPs, with 16S rDNA sequence analysis showing a 99.10% similarity to Micrococcus lylae. Characterization via UV–Vis, FTIR, XRD, and SEM–EDX confirmed that the CuNPs were spherical-shaped and ranged in size from 20 to 100 nm. These nanoparticles demonstrated antimicrobial effects against various bacteria. The cell free extract/CuNPs and biomass/CuNPs of the degrading Marinospirillum alkaliphilum strain N achieved 100% degradation of Acid Red 88 within 11 h. In contrast, cell free extract and the biomass of strain N alone required 24 h to achieve the same result. FTIR and GC–MS analyses verified the degradation of AR88 dye. Toxicity assessments using Artemia salina and radish seeds revealed that Acid Red 88 dye was toxic. In contrast, metabolite biodegradation and CuNPs exhibited low toxicity, no mortality of A. salina, and no inhibiting seed germination.